Hybrid fixation for repair of dual forearm fractures of adolescent patients: A case report and literature review : Hibridna oskrba zloma podlahti pri mladostniku: reprezentacija primera in pregled literature - Movrin, Igor (Acta Medico-Biotechnica, 2024)
Purpose: To assess hybrid fixation as an alternative option for repair of dual forearm fractures of adolescent patients. Case presentation: An 11-year-old boy presented with trauma to his right forearm resulting from playing on a trampoline. X-ray examinations confirmed fractures of both the right ulna and radius. Closed reduction and internal ESIN (elastic stable intramedullary nailing) fixation was selected for repair of the radius. Closed reduction of the ulnar fracture was unsuccessful, thus open reduction was performed. However, due to instability of the ulnar fracture after open reduction, internal plate fixation of the ulna was selected. At 3 months after surgery, the patient demonstrated full range of motion with no pain.
Keywords: forearm fractures; hybrid fixation; elastic stable intramedullary nailing (ESIN); open reduction in internal fixation